HUBUNGAN PROGRAM ONLINE ONSITE DENGAN KEPUASAN MASYARAKAT PADA BADAN PENYELENGGARA JAMINAN SOSIAL KETENAGAKERJAAN CABANG TONDANO - GABRIEL ESTER KAWULUR; SALMIN DENGO; NOVVA PLANGITEN (Sam Ratulangi University, 2022)
This study aims to determine the relationship between the Onsite Online Service Program and CommunitySatisfaction at the Tondano Branch of the Employment Social Security Organizing Agency. This study usesa quantitative descriptive research method with Chi Square data analysis techniques or also known as ChiSquare. Existing data obtained is from the distribution of questionnaires / questionnaires to 40 respondents.Chi square analysis was carried out by testing nominal or discrete data from the output of the questionnaireand processed using the statistical analysis program IBM SPSS Version 26.0. The results of this studyindicate the relationship or relationship between variable X onsite Online Service Program and variable Y.Community satisfaction is at a moderate level (the result of the Chi Square Count) by analyzing theContingency Correlation Coefficient. This is associated with the factors that influence the level ofrelationship between the Onsite Online Service Program and Community Satisfaction. Namely, theuncertain period of the pandemic, facilities and infrastructure such as supporting technology, supportingfacilities, but also the individual capabilities of BPJSTK participants in which there is an age factor.Keywords: Onsite Online Service Program, Community Satisfaction, Chi Square Analysis